Analisis Prinsip 5C untuk Meminimalisir Kredit Macet pada BUMDEsa Amanah Perspektif Syariah di Desa Bukit Gajah - Anisa Sulistiya; Muli Prima Aldi; Viras Alti Pidola; Tika Widiyan (CV. Kalimasada Group, 2025)
Bad debts are a serious problem in the management of BUMDEsa, so the application of the 5C principle is needed to assess the eligibility of prospective debtors and maintain the sustainability of financing. This study aims to analyze the application of the 5C principle in minimizing bad debts at BUMDEsa Amanah Desa Bukit Gajah as an effort to maintain the sustainability of financing. This type of research is qualitative. Data collection techniques, namely using observation, interviews, documentation. Data were obtained from the results of observations, interviews, and documentation. Based on the data collected starting from the results of observations, it can present the answer